A Novel Computational Framework for Visual Snow Syndrome - Damiano Perri; Osvaldo Gervasi (IEEE Access)
Visual Snow Syndrome (VSS) is a neurological condition that impairs the perceived image by causing the appearance of numerous constantly flickering dots, similar to those seen on a television screen that does not receive the antenna signal properly. This article presents two innovative applications using emerging technologies to help people suffering from VSS. One is based on Augmented and Virtual Reality to simulate the visual perception experienced by people affected by such syndrome in real time on the image sequence acquired by a smartphone’s camera. The other is based on a web platform based on a Virtual Reality engine, designed to create exercises parametrically to improve the UX and the usability of an experimental therapy that aims to alleviate the syndrome’s symptoms. We present the architecture of the two systems, which is characterised by a very simple yet very effective approach and use, as documented by the comments made by users. The results of an evaluation questionnaire submitted to volunteers who tested and scored the mobile App and eventually expressed opinions and suggestions are reported. The questionnaire results show users’ positive appreciation, as they outline in their comments how important it is for patients to have simulation tools that allow them to better explain their pathologies.